DNA damage response and cell cycle regulation in bacteria: a twist around the paradigm - Misra, Hari Sharan; Rajpurohit, Yogendra Singh (Frontiers in Microbiology, 2024)
The co-protease activity in RecA-ssDNA complex cleaves auto-repressor LexA resulting to the de-repression of a large number genes under LexA control. This process is called SOS response and genes that are expressed in response to DNA damage are called SOS genes. The proteins encoded by SOS genes are involved in both DNA repair and to keep the functions of crucial cell division protein (e.g. FtsZ) under check, till the damaged DNA is presumably repaired. This mechanism of SOS response is the only known mechanism of DNA damage response and cell cycle regulation in bacteria. However, there are bacteria that do not obey this rule of DNA damage response and cell cycle regulation, yet they respond to DNA damage, repaired it and survive. That means, such bacteria would have some alternate mechanism(s) of DNA damage response and cell cycle regulation beyond the canonical pathway of SOS response. Here, we present the perspectives that bacteria may have the other mechanisms of DNA damage response and cell cycle regulation mediated by bacterial eukaryotic type Ser/Thr protein kinases, as an alternate to the canonical SOS response, and herewith elaborate it with a well-studied example in the radioresistant bacterium Deinoocccus radiodurans.